(untitled) (Archive of Conferences, 2021)
The hypothesis of the research is the assumption that family traditions will influence the development of the creativity of a younger student if the family values are types of creative activities, collective creativity in the family, communication and dialogue between generations, provided the traditional continuity of family creativity, developed intrafamily relations, and creative interaction of members families under the influence of psychological factors: the ability for creative activity, the need for creative self-expression, personally significant results of family creativity. The methodological basis of the study was made up of theoretical studies of mental phenomena based on a systematic approach to their understanding (V.P. Zinchenko, B.F. Lomov, S.D.Smirnov, etc.), fundamental works in the field of psychology of personal creativity (D.B. Bogoyavlenskaya, L.S.Vygotsky, Ya.A. Ponomarev and others), the theory of reflection in psychological science (K.A. Abulkhanova-Slavskaya, S.L. Rubinstein, E.V. Shorokhova, etc.), theoretical provisions on the unity of consciousness and activity (A.G. Asmolov, A.N. Leont’ev, V.A.Petrovsky and others), the main provisions of the theory of personality subjectivity (EH Volkova, S.L. Rubinstein, E.A. Uvarov, etc.) , theory of personality and collective development (B.G. Ananiev, A.G. Asmolov, S.N. Konyshkova, etc.).